Membangun Lingkungan Belajar yang Kondusif: Evaluasi dan Solusi untuk Perbaikan Sarana dan Prasarana Sekolah Dasar Negeri Sukajadi 04 Kabupaten Bekasi Provinsi Jawa Barat - Baharuddin, Baharuddin; Muthi, Ibnu; Haryono, Pauzan (SENTRI: Jurnal Riset Ilmiah, 2025)
The condition of adequate facilities and infrastructure in elementary schools is essential to support an effective learning process. This research aims to identify the condition of facilities and infrastructure at SDN Sukajadi 04, Bekasi Regency, and offer appropriate improvement solutions. This research is based on the importance of a conducive learning environment to support students' academic achievement and teacher productivity. The methodology used in this study includes direct observation of the physical condition of school facilities, interviews with teachers and school staff, and documentation of current conditions through photographs and field notes. Observations were carried out to directly assess the condition of facilities and infrastructure, interviews to gain perspectives from facility users, and documentation to record visual evidence and written records regarding the condition of facilities. The results of the study showed that the classrooms at SDN Sukajadi 04 had dirty walls, desks, and chairs that were not suitable for use, and low-quality equipment. The Principal, Teacher, and Administration rooms are combined into one room with poor conditions, reducing comfort and productivity. Improper toilets and muddy fields when it rains are also major problems. This study concludes that the condition of inadequate facilities and infrastructure hinders the learning process and the performance of school staff. The implication of these findings is the need for improvements and upgrades to facilities through fundraising strategies, renovation planning, and ongoing maintenance to create a better and more comfortable learning environment. The implementation of this improvement is expected to improve the quality of education and welfare of the entire school community at SDN Sukajadi 04, Bekasi Regency.